Si‐nanoparticle synthesis using ion implantation and MeV ion irradiation. Issue 12 (21st August 2015) - Chulapakorn, T.; Sychugov, I.; Suvanam, S. S.; Linnros, J.; Wolff, M.; Primetzhofer, D.; Possnert, G.; Hallén, A.
Abstract: A dielectric matrix with embedded Si‐nanoparticles may show strong luminescence depending on nanoparticles size, surface properties, Si‐excess concentration and matrix type. Ion implantation of Si ions with energies of a few tens to hundreds of keV in a SiO2 matrix followed by thermal annealing was identified as a powerful method to form such nanoparticles. The aim of the present work is to optimize the synthesis of Si‐nanoparticles produced by ion implantation in SiO2 by employing MeV ion irradiation as an additional annealing process. The luminescence properties are measured by spectrally resolved photoluminescence including PL lifetime measurement, while X‐ray reflectometry, atomic force microscopy and ion beam analysis are used to characterize the nanoparticle formation process. The results show that the samples implanted at 20%‐Si excess atomic concentration display the highest luminescence and that irradiation of 36 MeV 127 I ions affects the luminosity in terms of wavelength and intensity. It is also demonstrated that the nanoparticle luminescence lifetime decreases as a function of irradiation fluence. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)